Effect of Glass Fiber Reinforcement on Mechanical Properties of Wood Material - Abdi Atilgan; Rabia Kocaer (BioResources)
Increasing the mechanical strength of wooden materials with glass fiber fabric reinforcement and composite elements can be a very suitable method for restoration and strengthening techniques in historical wooden structures. In this study, the effects of fiber-reinforced laminated wood composites were examined with respect to bending strength and modulus of elasticity in bending. Experimentally, 0°/90° woven glass fiber fabrics with areal weights of 200, 300, and 400 g/m² were bonded using epoxy resin to the longitudinal surfaces of two different wood species (Scots pine and Turkish beech). An evaluation of the bending properties of these wooden sandwich structures revealed that the incorporation of glass fiber fabric reinforcement led to a significant enhancement in their bending strength. In addition, a significant improvement was achieved in the modulus of elasticity. It was observed that glass fiber fabric, especially the 400 g/m² weight options, increased the durability of wood materials more. As a result, the bending strength of wood materials can be significantly increased with glass fiber fabric reinforcement. This method can be considered a promising reinforcement technique, particularly in the fields of engineering and construction. However, in the context of historical restoration, the use of external reinforcement must be approached with caution due to conservation principles such as material authenticity, reversibility, and minimal intervention.